Simulasi Hidrodinamika pada Tikungan Sungai Wonokromo Surabaya Menggunakan Delft3D - Akhmad Fauzi Almudhoqi; Andi Patriadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the existing hydrodynamic conditions at the bend of the Wonokromo River using the Delft3D numerical model. The simulation was conducted over 24 hours using topographic, bathymetric, tidal, and  flow data with a 10-year return period. The simulation results showed a maximum tide of 1.526 m and a minimum tide of -1.078 m relative to Mean Sea Level (MSL). The maximum flow velocity at the observation point reached 1.104 m/s, while the minimum velocity was 0.607 m/s. Model validation results yielded a Nash-Sutcliffe Efficiency (NSE) value of 0.853 and an RSR of 0.384, which fall into the "Very Good" category. Based on these results, the Delft3D model is capable of representing the existing hydrodynamic conditions of the Wonokromo River well.